GEOSPATIAL FLOOD RISK MAPPING AND VULNERABILITY ASSESSMENT USING GIS AND AHP IN HADEJIA RIVER BASIN, JIGAWA STATE, NIGERIA - Abubakar, Ahmed; Sani, Mubarak; Ahmad, Mohammad Hadi; Gambo, Jibrin (FUDMA Journal of Sciences, 2025)
Geographic Information System (GIS) and the Analytic Hierarchy Process (AHP) model within a multi-criteria decision analysis framework is used to map flood susceptibility in a river basin in northern Nigeria. Ten hydro-geomorphological indices, elevation, slope, rainfall, land use, and soil type, were systematically analyzed for their impact on flood hazards. A comprehensive flood susceptibility map was generated by assigning weights and ranks to factors. Areas with heightened vulnerability to flooding are attributed to slope, land use patterns, and proximity to water bodies. This study emphasizes the influence of rainfall patterns, drainage density, distance from rivers, geology, soil composition, topographic wetness, stream power, land use, encroachment onto flood plains, and vegetation cover on flood susceptibility. Additionally, gender considerations in disaster response and resilience efforts are discussed, highlighting challenges in flood-prone areas and advocating for inclusive strategies to bolster community resilience. The findings are pivotal for devising flood management strategies and hold applicability to analogous flood-prone areas globally.
Keywords: Flood susceptibility; Flood mitigation; Flood vulnerability; Flood-prone areas; Gender; Floods